2018
DOI: 10.1093/biolre/ioy001
|View full text |Cite
|
Sign up to set email alerts
|

The role of endoplasmic reticulum aminopeptidase 2 in modulating immune detection of choriocarcinoma†

Abstract: Gestational choriocarcinomas are derived from placental trophoblast cells, with HLA-C being the only class I polymorphic molecule expressed. However, choriocarcinomas have not been profiled for endoplasmic reticulum aminopeptidase 2 (ERAP2) expression. ERAP2 trims peptides presented by human leukocyte antigens (HLA) that have shown to modulate immune response. Over 50% of choriocarcinomas we screened lack ERAP2 expression, which suggests that the absence of ERAP2 expression allows immune evasion of choriocarci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 28 publications
2
16
0
Order By: Relevance
“…Subsequently, the CD56+ NK cells were differentiated into Dim/Bright ratio, with CD16 to distinguish the cytotoxicity. Most importantly, the ratio of activated NK cells characterized by CD69+/CD56 Dim /CD16+, where the cytotoxicity of this population has been demonstrated in a previous in vitro study, was almost doubled in PE (12.7 vs. 23%; Figure 4C) (12). This suggests that activated and more cytotoxic NK cells are circulating in women with PE.…”
Section: Immune Populations In Normotensive Controls and Pre-eclampsisupporting
confidence: 71%
See 2 more Smart Citations
“…Subsequently, the CD56+ NK cells were differentiated into Dim/Bright ratio, with CD16 to distinguish the cytotoxicity. Most importantly, the ratio of activated NK cells characterized by CD69+/CD56 Dim /CD16+, where the cytotoxicity of this population has been demonstrated in a previous in vitro study, was almost doubled in PE (12.7 vs. 23%; Figure 4C) (12). This suggests that activated and more cytotoxic NK cells are circulating in women with PE.…”
Section: Immune Populations In Normotensive Controls and Pre-eclampsisupporting
confidence: 71%
“…Collection and preparation were previously described (12). Red blood cells were lysed using ice-cold deionized water for 30 s. White blood cells were then resuspended in FACs buffer [1× phosphate buffered saline (PBS), 2% heat-inactivated fetal bovine serum (FBS)], counted, and blocked for 10 min in FACS Buffer and Human Trustain FcX Fc receptor blocking solution (Biolegend; #422302) at room temperature, followed by staining with CD3-APC/Fire750 (BioLegend; #344840), CD56-PE (BioLegend; #318306), CD8-PerCP (BioLegend; #344708), CD11a-PE/Cy7 (BioLegend; #301220), CD16-FITC (BioLegend; #302006), CD69-APC (BioLegend; #310910).…”
Section: Immune Populations In Normotensive Controls and Pre-eclampsimentioning
confidence: 99%
See 1 more Smart Citation
“…Lack of ERAP2 expression in haplotype B is because of the ERAP2 gene rs2248374 polymorphism that in uences on the RNA stability (15). It has been reported that there is a strong LD between haplotypes A and B of ERAP2 SNPs, which can be involved in the immune evasion of trophoblasts (30). Lack of ERAP2 expression has been proposed to be protective in AS and other in ammatory disorders (31).…”
Section: Discussionmentioning
confidence: 99%
“…9661L, Cell Signaling) (24,53,55), and ␤-actin (as a loading control, 1:1,000, catalog no. 4967L, Cell Signaling) (12,32,54) for 3 h at room temperature or overnight at 4°C. Membranes were then washed and incubated with the appropriate secondary antibody for 1 h at room temperature.…”
Section: Methodsmentioning
confidence: 99%